Marine-Derived Bisindole Alkaloid (R)-6'-Debromohamacanthin B as a Dual-Acting Anti-Pathogenic Agent that Targets Pseudomonas aeruginosa Virulence, Biofilm Formation, and Host Immune Responses - Huiyan Li (22529084) (2025)
P. aeruginosa is a refractory pathogen with strong quorum sensing (QS)-regulated virulence, biofilm formation, and the ability to induce harmful inflammation in the host. To develop a strategy that minimizes the risk of resistance development, we identified the marine-derived bisindole alkaloid (R)-6'-debromohamacanthin B (RDB) as a potent anti-pathogenic compound.